Vestibular perceptual testing from lab to clinic: a review - Grove, Colin R.; Klatt, Brooke N.; Wagner, Andrew R.; Anson, Eric R. (Frontiers in Neurology, 2023)
Not all dizziness presents as vertigo, suggesting other perceptual symptoms for individuals with vestibular disease. These non-specific perceptual complaints of dizziness have led to a recent resurgence in literature examining vestibular perceptual testing with the aim to enhance clinical diagnostics and therapeutics. Recent evidence supports incorporating rehabilitation methods to retrain vestibular perception. This review describes the current field of vestibular perceptual testing Vestibular Perception Review 2 This is a provisional file, not the final typeset article from scientific laboratory techniques that may not be clinic friendly to some low-tech options that may be more clinic friendly. Limitations are highlighted suggesting directions for additional research.